Supervision Of Bonded Area Facility Policies For Importers At The Bekasi Customs And Excise Intermediate Type A Supervision And Service Office For 2018-2019 - Pramukty, Rachmat; Harjo, Dwikora; Yulaeli, Tri; Titik Wiyani, Natalia; Adharyanto, Alpandi (International Journal of Educational Research & Social Sciences, 2022)
One particular phenomenon in this research is that the Bonded Zone facility policy has its own appeal in the producers' eyes on an export basis. Consequently, judging from the large number of Bonded Zone scattered throughout Bekasi City, it becomes a significant obstacle for the supervisory duty’s implementation. The number of personnel within the Directorate General of Customs and Excise (DJBC) is inadequate, which in turn, causes the practice of misusing DJBC's superior facilities is easier to do. This study aims to determine and analyze the Bonded Zone facility policy supervision for importers at the supervision and Service Office for Customs and Excise in Type A of Bekasi Customs and Excise and the constrictions and efforts in the supervision process. The research method employed was descriptive research with a qualitative approach. Meanwhile, the data analysis method implemented was qualitative data analysis. The results of this study indicated that the policy supervision of Bonded Zone facility for importers at KPPBC TMP A Bekasi has been going well on each year. However, it has not been optimally implemented. It is indicated by the findings from the inspection results and action carried out by KPPBC TMP A Bekasi. In implementing the bonded area facility policy supervision, KPPBC TMP A Bekasi tackled various obstacles, nearly data retrieval problems on the CEISA TPB application, the unmatched company IT Inventory to what was reported, and the insufficient number of personnel in the supervisory unit.